Conducting effective research into state complicity in human rights abuses. Issue 2 (2nd April 2020) - Blakeley, Ruth; Raphael, Sam
ABSTRACT: This paper explores how to conduct effective research into state complicity in human rights abuses. This type of research is challenging: the secretive nature of state violence presents considerable difficulties for the researcher, in terms of both access to evidence, and the safety and security of the researcher and victims. Recent developments in the methods and types of data available present new opportunities for strengthening research. Drawing on our own experience, specifically our work to map the CIA's rendition, detention and interrogation programme, we aim to show how we have navigated the difficult terrain of human rights investigation. The paper begins by exploring a number of challenges involved. We then discuss recent developments in human rights investigation techniques, as well as the emerging body of critical scholarship that is beginning to shape this kind of work among practitioners and academics alike. We consider some of the imbalances of power that affect this type of research. We then demonstrate how we tried to embrace new opportunities, while being mindful of the risks involved and the limitations of what we can achieve. We close with some reflections on ways forward for this type of research.